Level of Effectiveness of Employee Competency Development Plans for Improving the Performance of Education Personnel at the University of Sebelas Maret - Evi Rakhmawati; Dian Susiani; Sri Santoso Sabarini (Jurnal Ilmiah Sumber Daya Manusia, 2023)
Competency development for employees or human resources is very important for an organization. This is to support employee performance so that their abilities increase. However, there are several problems in the process of improving employee performance. This study aims to describe the effectiveness of the declaration of government programs in the form of filling in data on employee competency development plans (HCDP) towards improving the performance of education staff at Sebelas Maret University. This study uses a type of qualitative research. The data and data sources in this study were derived from interviews with informants, namely education staff with status as civil servants and non-PNS at Sebelas Maret University. Data were analyzed by source triangulation. The analysis technique goes through the stages of data collection, data reduction, data presentation, and drawing conclusions. The research results show that the employee competency improvement program is not effective, which indicates that the education staff at Sebelas Maret University are not interested in developing either their competence or their career.